Keterkaitan Isi Siaran Televisi di Indonesia dan Keadilan Informasi - Erni Herawati (Humaniora, 2012)
Indonesian Television Broadcasting has been progressing rapidly both in number of television stations and programs. In fact, almost all of national private televisions broadcasting programs were always about Jakarta. Article aimed to analyze on how the function of media which was not only provided information but it also supported the values of community and its sustainability. It related to the media content. The media content was not only determined by internal media factors but also the external ones. Finally, the owners of the media became the one who determined how media content was produced and formed. Therefore, to avoid information which was not monopolized by one party, the community should have various informations to choose. Finally, it is concluded that rules in broadcasting television has to consider the equality of information for people